1983
DOI: 10.1203/00006450-198306000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Airway Resistance, Airway Conductance, Specific Airway Resistance, and Specific Airway Conductance in Children

Abstract: SummaryIn 82 healthy children and in asthmatic children before and during positive allergen provocation test, airway resistance (Raw), airway conductance (G,), specific airway resistance (SR,), and specific airway conductance (SG,) were measured by body plethysmography during quiet breathing. Raw over total flow range (Raw t) and Raw at a flow rate of 0.5 liter/sec (Raw 0.5) are compared: Raw 0.5 is 10.3% smaller and shows a smaller coefficient of variation in healthy children. This is interpreted as a less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…We have found that this method greatly improves the acceptability of the plethysmographic procedure in young children without introducing bias to the estimate of sRaw or loss of reproducibility. 9 The mean sRaw VЈmax (1.1 kPa и s) observed in the present study is higher than in other studies, which have reported values ranging from 0.45 to 1.0 kPa и s. 8,13,14,20 This discrepancy can probably be ascribed to the fact that we, in contrast to most previous workers, used a plethysmograph with electronic BTPS compensation, which has introduced a positive frequency dependence and has resulted in significantly higher estimates of sRaw in comparison with measurements obtained with a heated rebreathing system to ensure BTPS conditions. 9 One of the advantages of sRaw ⌬Vmax and sRaw VЈmax is that these two measures can be estimated irrespective of the magnitude of the flow, and they are therefore applicable to subjects of all ages.…”
Section: Lung Function In Healthy Young Childrencontrasting
confidence: 70%
See 1 more Smart Citation
“…We have found that this method greatly improves the acceptability of the plethysmographic procedure in young children without introducing bias to the estimate of sRaw or loss of reproducibility. 9 The mean sRaw VЈmax (1.1 kPa и s) observed in the present study is higher than in other studies, which have reported values ranging from 0.45 to 1.0 kPa и s. 8,13,14,20 This discrepancy can probably be ascribed to the fact that we, in contrast to most previous workers, used a plethysmograph with electronic BTPS compensation, which has introduced a positive frequency dependence and has resulted in significantly higher estimates of sRaw in comparison with measurements obtained with a heated rebreathing system to ensure BTPS conditions. 9 One of the advantages of sRaw ⌬Vmax and sRaw VЈmax is that these two measures can be estimated irrespective of the magnitude of the flow, and they are therefore applicable to subjects of all ages.…”
Section: Lung Function In Healthy Young Childrencontrasting
confidence: 70%
“…In keeping with other investigators, we found no significant correlation between sRaw and either age, weight, or height. 8,13,14 We measured sRaw by a single-step procedure from the relation between variations of respiratory flow and variations of plethysmographic volume during normal breathing. The single-step procedure obviates the need for measuring breathing efforts against a closed shutter.…”
Section: Lung Function In Healthy Young Childrenmentioning
confidence: 99%
“…It does not rely on maximal expiratory effort and may thus be particularly suitable for older patients. Its value in the assessment of asthma in children has long been established, 53 but no studies examining the feasibility of this technique in older patients have been performed, so it is not routinely encountered in clinical practice. This represents an area for future studies to address validity and practicality of these techniques to assess airway obstruction in older patients.…”
Section: Diagnostic Difficulties and Options With Pftmentioning
confidence: 99%
“…From these observations it would seem that in airway obstruction, the diagnostic yield from the single-step procedure is comparable to that of the combined measurement of Raw and TGV. Yet another advantage of measuring sRaw is that beyond infancy sRaw is largely independent of body size [22][23][24], facilitating the interpretation of measurements carried out longitudinally in individual children.…”
Section: Discussionmentioning
confidence: 99%